Language-in-Education Policy in Zambia: The Case of Teaching in A Regional Official Language at A Selected Mission School in Lusaka - Kelvin Mambwe; Naomi Njobvu (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
Upon gaining independence in 1964, the Zambian government embraced English as the official language for education, media, legislation, and all governmental functions. This choice followed extensive discussions on whether to adopt English or a Zambian language as the national language for classroom instruction. Despite arguments in favour of both English and Zambian languages, English ultimately prevailed. This paper delves into the language-in-education policy, with a particular focus on the 2014 Zambia education policy. The study's main objective is to investigate the impact of using Cinyanja, a regional official language, as the medium of classroom instruction for teachers and learners at a selected mission (private) school in Lusaka. Qualitative data was gathered from the school, with four teachers and twenty learners randomly selected from a population of 200 and interviewed individually. Additionally, direct observation was employed as a data collection method. The study revealed that implementing the revised 2014 education policy is challenging because the language used for teaching is considered a second language yet the teaching/learning methods and materials are designed for first language learners. This presents a hurdle for teachers and learners, who must grapple with learning both the language of instruction and the subject matter.